The desire to age in place among older Australians - Australian Institute of Health and Welfare (Australian Institute of Health and Welfare, 2013)
Many older Australians report a desire to age in place. This bulletin explores the relationship between this desire and the housing circumstances of older Australians of different tenure types; that is, those who own their home outright, those paying a mortgage and those who rent their home either privately or through social housing.
Bulletin no. 114. Cat. no. AUS 169
Keywords: Ageing -- Housing; Housing -- Intentions; Housing, communities and neighbourhoods; Ageing; Housing; Housing; Intentions; Housing, community and neighbourhoods